"Breakthroughs": Engaging Literary "Voices" of Women Writers from the Southern African Region. Issue 1 (2nd January 2016) - Khan, Khatija BiBi
Summary: The aim of this article is to critically engage women's oral and literary productions from the southern Africa region. This article is christened "breakthroughs" for several reasons. First, it should be taken as a major breakthrough for women of southern Africa to have grouped together and speak with one "voice" by offering new and "fresh" ways of writing a variety of histories and narratives against the backdrop of the suffocating discourses of colonialism, neocolonialism, patriarchy, racism and sexism. The second breakthrough is derived from the desire of women to redress the imbalance in southern African literary and historical anthologies and accounts, given that writing and performing were and still are generally associated with men. Thus, writing and performance in this article are taken as "political" statements that women are making in the process of telling their stories rather than remaining cloistered in male-sanctioned discourses. The third breakthrough is located within the Pan-African spirit informing the "Women Writing Africa Project", which draws exclusively from women's experiences in West Africa, North Africa, East and southern Africa. Although this article purposively sampled the literary works of some women included in Volume I of the project, it is hoped that the analysis of the selected literary works shall be treated as one of the "major breakthroughs" in which works written "only" by women are brought under the academic spotlight.